A study on awareness of household waste separation in Parit Raja, Batu Pahat, Johor: rural areas - Ali, R.; Ariffin, N.S.M.; Ang, P.S.E; N.Y., Zainun; Sunar, N.M.; Hamid, Nurul Hidayati; Hamidon, Nuramidah; Harun, Hasnida; Muhamad, Mimi Suliza; Leman, Abdul Mutalib (Penerbit Uthm, 2018)
Malaysia is embarking on green initiatives which have been expressly stipulated in the Eleventh Malaysia Plan (2016-2020). In order to transform ideas into reality, the government has identified six strategic thrusts and six game changers that will help Malaysia to stay ahead of global challenges and opportunities in the next five years. In one of the strategic thrusts, the government has planned a greener trajectory for sustainability and resilience [1]. As a result, governmental agencies such as the Department of Environment (DOE) has been given the mandate to conserve and protect the environment and its natural resources for present and future generations. Among the ways applied by the government for solving environmental problems, especially waste generation, include waste minimization, compost and incineration. The Public Cleansing Management Act 2007 (SWPCM Act 2007) came into force on 1 September 2011. It was administered by the Ministry of Housing and Local Government. The main objective of the act is to regulate the management of controlled solid waste and to ensure high-quality services in solid waste management [2]. Apart from the government, the community should also play its role in minimizing waste generation at household level.